2011
DOI: 10.1177/0145445510393731
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of a Group Curriculum for Parents of Young Children With Disruptive Behavior

Abstract: This study examined effectiveness of a Group Curriculum (GC) for parents of 3- to 6- year-old children with disruptive behavior. The curriculum is based on the book Parenting the Strong-Willed Child. A total of 39 parents were randomly assigned to the GC condition or a wait-list control condition. Assessments occurred at baseline, postintervention (6 weeks after baseline), and 2-month follow-up. Findings indicated that the GC condition was associated with lower levels of child problem behavior and improved par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In behavioral parent-training programs, the primary outcome is child behavior change. Previous research indicated that, relative to a control group, the GC intervention examined in this study does lead to decreases in parent reports of child disruptive behavior (Forehand et al, 2011). Although a control group was not included in the current investigation, the findings suggested that child disruptive behaviors decreased to near-normative levels.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In behavioral parent-training programs, the primary outcome is child behavior change. Previous research indicated that, relative to a control group, the GC intervention examined in this study does lead to decreases in parent reports of child disruptive behavior (Forehand et al, 2011). Although a control group was not included in the current investigation, the findings suggested that child disruptive behaviors decreased to near-normative levels.…”
Section: Discussionmentioning
confidence: 68%
“…Child management skills covered in the six sessions consist of skills intended to reduce negative parent-child interactions by increasing attending and verbal rewarding for desirable child behavior, ignoring undesirable child behavior, providing clear instructions to the child, and using time-out for noncompliance and positive reinforcement for compliance (see Forehand et al, 2011, for more details). Parents are given weekly homework assignments that focus on practicing the skills at home with their child.…”
Section: Group Curriculum (Gc)mentioning
confidence: 99%
“…For example, in a community-based study, Pavuluri et al (1996) found that, in their sample, there were parents who sought help even when they did not think their child had a problem. Thus, in community-based parenting programs, some parents seeking help report young children's disruptive behaviors at or above established clinical cutoffs (e.g., Forehand et al 2011) whereas other parents, similar to those in the Pavuluri et al study, report levels of these behaviors that are more congruent with normative levels of disruptive behavior problems (Cunningham et al 2000).…”
Section: Introductionmentioning
confidence: 75%
“…The participants were selected from 91 parents who enrolled in one of two studies to learn parenting skills to decrease their 3-to 6-year-old child's disruptive behaviors Forehand et al 2011). The criteria for inclusion in both studies were as follows: (a) having a 3-to 6-year-old child, (b) English as a first language, and (c) at least 50% legal custody with the child living with the parent at least 5 of 7 days per week for the next two and one-half months.…”
Section: Participantsmentioning
confidence: 99%